DIFFERENCES BETWEEN B2B AND B2C CUSTOMER RELATIONSHIP MANAGEMENT. FINDINGS FROM THE CZECH REPUBLIC - Kolis, Karel; Jirinova, Katerina (European Scientific Journal, ESJ, 2014)
The purpose of this article is a comparison between Customer relationship management (CRM) in the B2B environment and B2C Environment. Literature shows significant differences; therefore the motivation of the research and hence the article was the verification of theoretical statements. Based on the literature review of CRM, an online questionnaire was sent. This research used 6 questions from the questionnaire. On a large number of respondents the differential analysis was made. Results prove the theoretical expectations: CRM in B2B and B2B environment are partially similar, but the mostly differs.